DEVELOPING MACROMEDIA FLASH AS AN ENGLISH TEACHING MEDIA ON SPEAKING NARRATIVE TEXT FOR THE TENTH STUDENTS AT SMA AZIZI MEDAN - Via Monica; Masitowarni Siregar (Universitas Negeri Medan, 2022)
The purpose of this research is to establish macromedia Flash as an English teaching medium for tenth grade students at SMA Azizi Medan.This research was carried out in six stages using Research and Development (R&D) design: obtaining data and information, analyzing data, designing media, validating by experts, amending, and delivering the final result.The research focused on SMA Azizi Medan's grade X.The information was acquired by interviewing an English teacher and sending a questionnaire to 30 students to determine their needs.The results of the interview and questionnaire revealed that students require a learning medium for teaching speaking that will assist them in comprehending the narrative text.Experts have supported macromedia flash as a learning media. The average score is 4.55. It means the developed learning media by using macromedia flash is relevant or appropriate and categorized as a very good learning media for students at SMA Azizi Medan.